2010
DOI: 10.1634/theoncologist.2010-s1-43
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues in Patient–Physician Communication About Therapy for Cancer: Professional Responsibilities of the Oncologist

Abstract: Value in cancer care from a patient-centered perspective not only requires full oncologist-to-patient communication of information about potential treatments, but also imbues in the oncologist a responsibility to evaluate the value of cancer therapies and to offer to patients only those potential therapies that are appropriate for the patient. A case is presented in which the possibility of a low-probability treatment presented without adequate context or advice led to a prolonged, unsatisfying death for a you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The goal of this discussion is to reach consensus over the realistic treatment options that can be offered to the patient to improve continuity of care and reduce internal disagreement over goals of care. Overly optimistic messages to patients, as well as overly pessimistic messages, can dramatically affect advanced care planning discussions with patients (120-124), patient decision making, well-being, and beneficent care (125).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…The goal of this discussion is to reach consensus over the realistic treatment options that can be offered to the patient to improve continuity of care and reduce internal disagreement over goals of care. Overly optimistic messages to patients, as well as overly pessimistic messages, can dramatically affect advanced care planning discussions with patients (120-124), patient decision making, well-being, and beneficent care (125).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Oncologists are in a unique position to develop a therapeutic relationship with a patient from the initial cancer diagnosis to prolonged survivorship and end of life. Physician relational attitude towards individual patients impacts the effectiveness of communication, patient satisfaction, treatment decisions, perceived quality of care and clinical outcomes (Bingley et al, ; Vries et al, ; Wenger & Vespa, ). Although several studies examined physician factors addressing patient preferences in cancer care, none reported the physician’s perception of the patient–oncologist relationship or its effect on subsequent medical recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients often develop relationships with several physicians across multiple medical subspecialties. However, the patient–oncologist relationship is instrumental in guiding important discussions across the course of cancer treatment that are vital to quality PCC, including challenging conversations, like the value of continuing treatment versus pursuing comfort‐focused, end‐of‐life care (Wenger & Vespa, ). This review highlights the dearth in studies examining relational perspective from both sides of the physician–patient dyad and how this may affect patient‐centred clinical discussions across the cancer trajectory such as diagnostic testing, treatment options, symptom management and the timing of hospice referral.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the life quality of the patient, the psychological distress of the family members who are involved in the patient's support should be improved. The physicians' goal is to help the patient's family face the anxiety and fears for patients with digestive cancers and also, the capacity to meet everyday problems (11). The impossibility of self-feeding in eso-gastric cancers, the presence of stomata for easier feeding, the presence of stomata for intestinal evacuation are challenging for patients.…”
Section:  the Physician's Responsibility In The Psychological Managementioning
confidence: 99%